The application and Heritage of Copper Drum Culture in Nanning Primary School Art Classroom - Wei Yangyang; Su Guiyu (Integrated Journal for Research in Arts and Humanities, 2022)
Copper drums have been baptized by thousands of years of wind and rain, and festival activities related to copper drums are still active in some regions of China, so it is of practical significance to study the inheritance and innovation of copper drum art. The heritage needs to start from children, and elementary school teachers need to let children receive the culture of copper drums from an early age and feel the important role of copper drums in national festival activities in order to better inherit the culture of copper drums and promote the wide circulation of traditional cultural symbols in Guangxi region. This study takes the art curriculum resources of Nanhu Elementary School as an entry point, explains from the perspective of developing regional folk art curriculum resources according to local conditions, and further considers how to transform the copper drum cultural resources into art curriculum resources by analyzing excellent cases of local school-based curriculum development and utilization, deepening students' sense of identification with their native art and making them consciously take up the mission of cultural inheritance and promotion.